Rancang Alat Otomatis Pengontrol Pintu Air Waduk Otomatis Mengatasi Bencana Banjir dengan Pemanfaatan Teknologi IoT - Martoga Mahulae; Marto Marto; Milli Alfhi Syari (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Floods are natural disasters that often occur in Indonesia and cause damage to property, infrastructure, and casualties. One of the main factors causing flooding is the failure of water management systems such as reservoirs to manage the sudden increase in water volume. This research aims to design an automatic reservoir sluice controller by utilizing Internet of Things (IoT) technology to reduce flood risk. The system uses a NodeMCU ESP8266 microcontroller and an HC-SR04 ultrasonic sensor to monitor the water level in real-time, as well as a servo motor that controls the sluices. The system is connected to the Blynk app, allowing remote monitoring and control of the sluice gates via mobile devices. This tool automatically adjusts the position of the sluice gate based on sensor data to keep the water level safe and reduce the potential for flooding. The test results show that this IoT-based automated system is able to work effectively in controlling sluice gates and can be used for flood disaster prevention in the surrounding environment.